“Where to touch them?” Representing the Ndebele in Rhodesian Fiction (Historia, 2021)
EnglishEarly missionaries and travellers who encountered Mzilikazi’s Ndebele invariably represented them as superior to other people in the far interior. Only when they were seen as standing between Britain and Mashonaland, did more hostile representations prevail and then they were reported not as noble, but as simple savages whose brutal raids destabilised the areas surrounding the Khumalo kingdom. The most influential fictional representation of an idealised Ndebele were the Kukuana of Haggard’s King Solomon’s Mines, who while being savages, showed a capacity for nobility from which the whites could learn. The Kukuana anticipated many subsequent fictional depictions of the Ndebele. Later novels often reproduced British South Africa Company propaganda and the changing representation of the Ndebele depended on whether the Company were in the process of invading Mashonaland, and later Matabeleland, or whether the Ndebele appeared to have submitted to the Company’s authority, or had rebelled against it. Some novelists represented the Ndebele as victims of the Company’s greed and misgovernment and in later Rhodesian novels they were shown as worthy allies of the new rulers of the southern Zambesian plateau who exercised the authority that had formerly been the prerogative of the Khumalo kings.    Afrikaans“Where to touch them?” Voorstellings van die Ndebele in Rhodesiese Fiksie Vroeë sendelinge en reisigers wat Mzilikazi se Ndebele teëgekom het, het laasgenoemde sonder uitsondering as meerderwaardig teenoor ander mense in die verre binneland uitgebeeld. Eers toe hulle tussen Brittanje en Masjonaland te staan gekom het, het meer vyandige voorstelings van hulle die lig gesien. In daardie stadium is hulle allermins as edel beskryf, maar eerder as eenvoudige barbare wie se gewelddadige strooptogte die gebied om die Khumalo-koninkryk gedestabiliseer het. Die invloedrykste fiktiewe voorstelling van die geïdealiseerde Ndebele is dié van die Kukuana in Haggard se King Solomon’s Mines wat, hoewel hulle barbare was, tog ŉ neiging tot edelheid openbaar het waaruit die blankes kon leer. Die Kukuana het talle latere fiktiewe uitbeeldings van die Ndebele voorafgegaan. Latere romans het dikwels propaganda vir die British South Africa Company (BSAC) verteenwoordig. Veranderende voorstellings van die Ndebele het dus afgehang daarvan of die BSAC besig was om Masjonaland, en later Matabeleland, in te val, en of dit gelyk het asof die Ndebele hulle aan die gesag van die BSAC onderwerp, of daarteen gerebelleer het. Sommige romanskrywers het die Ndebele as slagoffers van die BSAC se gierigheid en wanadministrasie uitgebeeld. In latere Rhodesiese romans is hulle selfs as waardige bondgenote van die nuwe regeerdes van die suidelike Zambesiese plato beskryf wat die gesag uitgeoefen het wat voorheen die prerogatief van die Khumalo-konings was.
Keywords: Bertram Mitford; colonial allegories; Lobengula; Mzilikazi; Ndebele; noble savage; Rhodesian fiction; Rider Haggard; savage; Zimbabwean fiction; Barbaar; edele barbaar; koloniale allegorieë; Rhodesiese fiksie; Zimbabwiese fiksie